2005
DOI: 10.1016/j.adolescence.2005.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of smoking as health and social risk in adolescence

Abstract: This investigation describes what smoking means to adolescents, and attempts to better understand it as a rite of passage. Applying a social ontology to an often‐individualized issue, interviews were conducted with 20 adolescent smokers between the ages of 13 and 19. Results show that adolescents possess detailed information about the risks of smoking. Both age and gender differentiated the meanings of smoking which were found to be both positive and negative. Valence inconsistency increased with age. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
3
16
0
3
Order By: Relevance
“…Piko and colleagues (2007) also found that the positive social appearance dimension played an important role when considering smoking, reporting that more smokers evaluated a typical smoker as e.g., "good-looking". These results illuminate the function of cigarette smoking as a visual marker, signalising adult style, individuality, sociability, rebellion, and peer group bonding (Amos, Gray, Currie, & Elton, 1997;Amos et al, 1998;Holm, Kremers, & de Vries, 2003;Tilleczek & Hine, 2006;Watson, Clarkson, Donovan, & Giles-Corti, 2003). Results also confirm the assumption that young adolescents (initiators) tend to regard social motives as most important (Baker, Brandon, & Chassin, 2004) for their smoking decisions e.g., as expressed by socially attractive features as opposed to more individual characteristics.…”
Section: Theoretical Considerations Targeting Smoker Imagessupporting
confidence: 71%
“…Piko and colleagues (2007) also found that the positive social appearance dimension played an important role when considering smoking, reporting that more smokers evaluated a typical smoker as e.g., "good-looking". These results illuminate the function of cigarette smoking as a visual marker, signalising adult style, individuality, sociability, rebellion, and peer group bonding (Amos, Gray, Currie, & Elton, 1997;Amos et al, 1998;Holm, Kremers, & de Vries, 2003;Tilleczek & Hine, 2006;Watson, Clarkson, Donovan, & Giles-Corti, 2003). Results also confirm the assumption that young adolescents (initiators) tend to regard social motives as most important (Baker, Brandon, & Chassin, 2004) for their smoking decisions e.g., as expressed by socially attractive features as opposed to more individual characteristics.…”
Section: Theoretical Considerations Targeting Smoker Imagessupporting
confidence: 71%
“…The present study showed that Saudi male university students have low awareness of the health risks of smoking. This is consistent with a finding on water-pipe smoking from a sample of Eastern Saudi secondary school (19), but differs from the results from western studies (20). Social and school education on antismoking without detailed knowledge about the relationship of mortality to smoking in Saudi Arabia might not produce an effective outcome.…”
Section: Discussionsupporting
confidence: 78%
“…Girls also expressed that smoking was an important means of forming and strengthening relationships and coping with negative emotions (Amos & Bostock, 2007). In a study with adolescent girls in northern Canada, differences in tobacco use were observed for older and younger girls; among younger girls (12 years and younger) smoking was socially adaptive, whereas among older (16-year-old) girls, smoking was used to manage stress and negative emotions (Tilleczek & Hine, 2006). A qualitative study with Aboriginal adolescent girls in Canada found that girls began smoking out of curiosity, as well as to deal with various forms of stress, including stress at school and in their families and communities, and experiences of discrimination and racism (de Finney et al, 2013).…”
Section: Acknowledging the Meanings Of Smoking For Womenmentioning
confidence: 99%